Caplaire Learning Model: An Effective Strategy to Improve Science Literacy Skills - Ananda, Lala Jelita; Suwandayani, Beti Istanti; Anggoro, Kiki Juli; Simanihuruk, Lidia; Ratno, Suyit (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
The issue of science literacy has gained significant importance in recent years, particularly as the world faces complex, technology-driven challenges that demand scientifically literate citizens. Science literacy, which encompasses the knowledge and skills needed to understand and engage with scientific concepts, is a critical element of modern education. However, despite its importance, many educational systems, particularly in developing countries, struggle to effectively enhance students' science literacy. This study aims to evaluate the effectiveness of the Caplaire Learning Model in improving science literacy among students in the elementary school teacher education program at Universitas Negeri Medan (UNIMED). The study uses a mixed-methods approach, incorporating both quantitative (pre-test and post-test) and qualitative (interviews and surveys) data collection techniques to assess the impact of the model. Findings indicate a significant improvement in students' scientific literacy following the implementation of the Caplaire model, with higher post-test scores and positive feedback from students and lecturers. The Caplaire model, which integrates inquiry-based learning and reflection, effectively engaged students and fostered a deeper understanding of scientific concepts. These results suggest that the Caplaire model can be a valuable tool for improving science literacy in teacher education programs, with potential implications for broader adoption in educational curricula.